2015
DOI: 10.1016/j.cyto.2014.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Serum IL-9, IL-17, and TGF-β levels in subjects with diabetic kidney disease (CURES-134)

Abstract: The role of inflammation in both diabetes and diabetic kidney disease (DKD) is becoming more widely accepted. However, the role of recently characterized T cell cytokines interleukin (IL)-9 and IL-17 in diabetes and especially DKD is less well studied. Transforming growth factor beta (TGF-β) controls the secretion of both of these cytokines. In this study, we estimated the levels of IL-9, IL-17, and TGF-β in the serum of subjects with normal glucose tolerance (NGT = 88) and subjects with type 2 diabetes withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 13 publications
1
34
0
Order By: Relevance
“…21 The increased levels of TGF-b1 is closely associated with the kidney damage, for example, the gene transfer of TGF-b1 in the mesangium of normal rats results in glomerulosclerosis, 22 the TGF-b1 production is increased in human kidney diseases such as diabetic nephropathy and allograft nephropathy. 23 In this sense, TGF-b1 overproduction is closely associated with the risk of CKD. Second, TGF-b1 secretion and production is genetically regulated.…”
Section: Discussionmentioning
confidence: 99%
“…21 The increased levels of TGF-b1 is closely associated with the kidney damage, for example, the gene transfer of TGF-b1 in the mesangium of normal rats results in glomerulosclerosis, 22 the TGF-b1 production is increased in human kidney diseases such as diabetic nephropathy and allograft nephropathy. 23 In this sense, TGF-b1 overproduction is closely associated with the risk of CKD. Second, TGF-b1 secretion and production is genetically regulated.…”
Section: Discussionmentioning
confidence: 99%
“…IL-9 also showed a positive correlation with urea and microalbuminuria. These results suggest the involvement of these cytokines in the DKD, but more studies are needed to further elucidate their role [109].…”
Section: Based On Cytokines Profile and Effector Function Cd4 + T Hementioning
confidence: 87%
“…Sirota et al (38) have demonstrated that plasma IL-8 is a biomarker of acute kidney injury. Vasanthakumar et al (39) suggested that IL-17 was positively and negatively correlated with fasting and postprandial glucose levels, respectively, and glycated hemoglobin (HbA1c) was observed in subjects with diabetic kidney disease. Ahuja et al (40) indicated that that circulating IL-6 mediates inflammatory responses via CXCL1 production following acute kidney injury in mice.…”
Section: Discussionmentioning
confidence: 99%